Effects on stone cell development and lignin deposition in pears by different pollinators - Yan, Chongchong; Zhang, Nan; Xu, Chao; Jin, Qing; Qi, Yongjie; Cai, Yongping (Frontiers in Plant Science, 2023)
The pear pulp is formed by the development of the ovary wall, which is the somatic cell of the female parent, and its genetic traits are identical to those of the female parent so its phenotypic traits should also be identical to those of the female parent. However, the pulp quality of most pears, especially the number of stone cell clusters (SCCs) number and degree of polymerization (DP), were significantly affected by the paternal type. Stone cells are formed by the deposition of lignin in parenchymal cell (PC) walls. However, studies on the effect of pollination on lignin deposition and stone cell formation in pear fruit have not been reported. In this study, 'Dangshan Su' P. bretschneideri Rehd.) was selected as the mother tree, while 'Yali' (P. bretschneideri Rehd.) and 'Wonhwang' (P. pyrifolia Nakai.) were used as the father trees to perform cross-pollination. We investigated the effects of different parents on SCCs number and DP, and lignin deposition by microscopic and ultramicroscopic observation. The results showed that the formation of SCCs proceeds was consistent in DY and DW, but the SCC number and DP in DY were higher than that in DW. Ultramicroscopy revealed that the lignification process of DY and DW were all from corner to rest regions of the compound middle lamella and the secondary wall, with lignin particles deposited along the cellulose microfibrils. They were alternatively arranged until they filled up the whole cell cavity to culminate in the formation of stone cells. However, the compactness of the wall layer of the cell wall was significantly higher in DY than in DW. We also found that the pit of the stone cells was predominantly single pit pair, they transported degraded material from the PCs that were beginning to lignify out of the cells. Stone cell formation and lignin deposition in pollinated pear fruit from different parents were consistent, but the DP of SCCs and the compactness of the wall layer were higher in DY than that in DW. Therefore, DY SCC had a higher ability to resist the expansion pressure of PC.